Pigs productivity depending on intensity of boar and sows growth in the breeding period - Зубенко, В. В. (Scientific Progress & Innovations, 2012)
The results of researches on the study of the productivity of pigs of large white breed depending on homo- and heterogeneous combination of boars and sows of different growth intensity in the period of their breeding. It has been established that the intensive breeding positively influences on their reproductive abilities, and also on growth and saving litter in the suckling period. Difference between І and ІV experimental groups was 37,3 a pigling. It is recommended to use boars and sows of the intensive breeding.